A large-scale study on the effectiveness of a Bacillus subtilis Ch-13-based biofungicide against green mould disease and mushroom yield improvement - Potočnik, Ivana S; Todorović, Biljana; Milijašević-Marčić, Svetlana; Luković, Jelena; Kanižai Šarić, Gabriella; Majić, Ivana; Rekanović, Emil (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
The aim of this study was to test a biofungicide based on Bacillus subtilis Ch-13 and its effectiveness in the control of green mould disease of cultivated mushroom in comparison with the fungicide prochloraz. Biofungicide effectiveness in disease control and impact on yield were evaluated on Agaricus bisporus after its natural infection with Trichoderma aggressivum in a commercial mushroom growing facility. An assay for testing the microbial efficacy of the biofungicide was conducted in two different procedures involving either three or two split doses. The highest statistically significant effectiveness in green mould control was shown by the fungicide prochloraz (71.43%), followed by the biofungicide applied in tree split doses (53.57%), and finally its two doses (45.46%). The biofungicide significantly improved yield in comparison with an untreated control and the fungicide prochloraz. Three split applications of B. subtilis strain Ch-13 enhanced mushroom yield to a larger extent than its two split doses, although the same final amount was used in both procedures. Biofungicide application in three split doses increased the total mass of harvested mushrooms 8.41% compared to the untreated control, and 10.53% compared to the fungicide prochloraz. These results implied that the biofungicide should be applied in three split applications: 30 ml (second day after casing) + 15 ml (two weeks after casing) + 15 ml (after first flush, 20-25 days after casing). The biofungicide B. subtilis Ch-13 should be further investigated regarding its joint usage with chemical fungicides in different application procedures, as it showed remarkable characteristics both in terms of promoting mushroom yield and inhibiting the spread of mycopathogenic T. aggressivum.